Pedagogical Interaction and Learning Performance as Determinants of Academic Achievement. (16th January 2015) - Costa, Cesário; Cardoso, Ana Paula; Lima, Margarida Pedroso; Ferreira, Manuela; Abrantes, José Luís
Abstract: This investigation aims to relate teacher competencies, student-student interactions and learning performance, and its direct and indirect effects on academic achievement of high school students. A quantitative research was carried out, involving a representative sample of 1986 students attending Secondary Education Schools located in the central region of Portugal. The results obtained through the structural model show that perceived teacher competencies influence student-student interactions and learning performance positively and significantly; student-student interactions positively and significantly influence the learning performance which, in turn, influences positively and significantly students' academic achievement. The established model provides insights for a better understanding of the importance of communication, in the context of the classroom, and of the students' learning involvement in the academic activities, towards the promotion of school success.